An Investigation of Palladium Oxygen Reduction Catalysts for the Direct Methanol Fuel Cell - G. F. Álvarez; M. Mamlouk; K. Scott (International Journal of Electrochemistry)
A comparative study of Pd and Pt was carried out in DMFC using different methanol concentrations and under different operating conditions. Cell performance was compared at methanol concentrations of 1, 3, 5, and 7 M and at temperatures of 20, 40, and 60°C. Homemade Pd nanoparticles were prepared on Vulcan XC-72R using ethylene glycol as the reducing agent at pH 11. The resulting catalyst, Pd/C, with metal nanoparticles of approximately 6 nm diameter, was tested as a cathode catalyst in DMFC. At methanol concentrations of 5 M and higher, the Pd cathode-based cell performed better than that with Pt at 60°C with air.